Aspergillus niger Secretes Citrate to Increase Iron Bioavailability - Odoni, Dorett I.; van Gaal, Merlijn P.; Schonewille, Tom; Tamayo-Ramos, Juan A.; Martins dos Santos, Vitor A. P.; Suarez-Diez, Maria; Schaap, Peter J. (Frontiers in Microbiology, 2017)
Aspergillus niger has an innate ability to secrete various organic acids, including citrate. The conditions required for A. niger citrate overproduction are well described, but the physiological reasons underlying extracellular citrate accumulation are not yet fully understood. One of the less understood culture conditions is the requirement of growth-limiting iron concentrations. While this has been attributed to iron-dependent citrate metabolising enzymes, this straightforward relationship does not always hold true. Here, we show that an increase in citrate secretion under iron limited conditions is a physiological response consistent with a role of citrate as A. niger iron siderophore. We found that A. niger citrate secretion increases with decreasing amounts of iron added to the culture medium and, in contrast to previous findings, this response is independent of the nitrogen source. Differential transcriptomics analyses of the two A. niger mutants NW305 (gluconate non-producer) and NW186 (gluconate and oxalate non-producer) revealed up-regulation of the citrate biosynthesis gene citA under iron limited conditions compared to iron replete conditions. In addition, we show that A. niger can utilise Fe(III) citrate as iron source. Finally, we discuss our findings in the general context of the pH-dependency of A. niger organic acid production, offering an explanation, besides competition, for why A. niger organic acid production is a sequential process influenced by the external pH of the culture medium.